Studying Risk Factors in the Formation and Development of Depressive States of the Involutionary Period - Shadmanova L. Sh. (Scientific Trends, 2025)
In recent decades, approaches to assessing the outcome of depressive distress in people of serotonin age have undergone significant changes. Along with the conservation of traditional methodology in defining categories of an outcome of depression and their division into the congenial and unfavourable bunches (Jhingan H.P., Sagar R., 2001; Baldwin R. Cand Gallagley A., 2006), representation about criteria of reference of each concrete variant of an outcome to one of these categories has extended.
Keywords: Depression, involuntary period, suicide, anxiety, adaptation.